Anopheles maculipennis Complex in The Netherlands: First Record of Anopheles daciae (Diptera: Culicidae) - A. Ibáñez-Justicia; Nathalie Smitz; Rody Blom; Ann Vanderheyden; Frans Jacobs; Kenny Meganck; Sophie Gombeer; Thierry Backeljau; Constantianus J. M. Koenraadt; J. S. Griep; Marc De Meyer; Arjan Stroo (Diversity, 2022)
Despite their past importance as vectors of indigenous malaria, the species composition and spatial distribution of the members of the Anopheles maculipennis complex have been studied to a limited extent in the Netherlands. Therefore, this investigation focuses on the distribution of the members of this complex in the Netherlands, including Anopheles daciae, which has recently been found in countries bordering the Netherlands. In the framework of a national mosquito surveillance between 2010 and 2021, a total of 541 specimens of An. maculipennis s.l. were analyzed from 161 locations covering the entire territory. In addition, 89 specimens were analyzed from overwintering sites during the winter of 2020/2021. All individual mosquitoes were identified to species-level using Sanger sequencing of the ribosomal internal transcribed spacer 2. To characterize the habitat of An. maculipennis s.l. in the Netherlands, land cover use data was extracted in a 1 km buffer area around each finding location. For populations collected in summers between 2010 and 2021, the most frequent species was An. messeae, present in 88.19% of the locations, followed by An. maculipennis s.s. (11.80%), An. atroparvus (3.72%) and An. daciae (3.72%). Anopheles daciae was found in the southern inland areas of the country. Furthermore, An. messeae and An. daciae occurred in sympatry at overwintering sites. This study provides relevant information on the occurrence of species of the Anopheles maculipennis complex in the Netherlands, contributing to a better estimation of the risk of mosquito-borne disease in the country.